Autoimmune pancreatitis - Davorin Dajčman (Zdravniški Vestnik, 2007)
Background: Autoimmune pancreatitis is a recently described type of pancreatitis of presumed autoimmune etiology. Autoimmune pancreatitis is often misdiagnosed as pancreatic cancer difficult, since their clinical presentations are often similar. The concept of autoimmune pancreatitis was first published in 1961. Since then, autoimmune pancreatitis has often been treated not as an independent clinical entity but rather as a manifestation of systemic disease. The overall prevalence and incidence of the disease have yet to be determined, but three series have reported the prevalence as between 5 and 6 % of all patients with chronic pancreatitis. Patient vary widely in age, but most are older than 50 years. Patients with autoimmune pancreatitis usually complain of the painless jaundice, mild abdominal pain and weight loss. There is no laboratory hallmark of the disease, even if cholestatic profiles of liver dysfunction with only mild elevation of amylase and lipase levels have been reported. Conclusions: Proposed diagnostic criteria contains: (1) radiologic imaging, diffuse enlargement of the pancreas and diffusely irregular narrowing of the main pancreatic duct, (2) laboratory data, elevated levels of serum ã-globulin and/or IgG, specially IgG4, or the presence of autoantibodies and (3) histopathologic examination, fibrotic change with dense lymphoplasmacytic infiltration in the pancreas. For correct diagnosis of autoimmune pancreatitis, criterion 1 must be present with criterion 2 and/or 3. Autoimmune pancreatitis is frequently associated with rheumatoid arthritis, Sjogren’s syndrome, inflammatory bowel disease, tubulointersticial nephritis, primary sclerosing cholangitis and idiopathic retroperitoneal fibrosis. Pancreatic biopsy using an endoscopic ultrasound-guided fine needle aspiration biopsy is the most important diagnostic method today. Treatment with corticosteroids leads to the and resolution of pancreatic inflamation, obstruction and pancreatic duct strictures.